2020
DOI: 10.14221/ajte.2020v45n8.2
|View full text |Cite
|
Sign up to set email alerts
|

Learning To Become An English Language Teacher: Navigating The Self Through Peer Practicum

Abstract: Pre-service English language teachers' school practicum is key to their learning to become a teacher. However, a number of challenges are observed in its implementation. This paper addresses this issue by investigating how engaging in practicum as peers can function as mentoring support and how this process can influence their selves. A cohort of 16 senior pre-service English teachers was invited to participate in the study from a state university in the west of Turkey. We collected qualitative data through di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 35 publications
(47 reference statements)
0
4
0
Order By: Relevance
“…In the beginning, they have some pre-conceptions about teaching that they confirm or discard. Finally, pre-service teachers provide emotional support and mutual motivation to each other (Comoglu and Dikilitas, 2020). The issues briefly narrated above correspond to face-to-face classes.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In the beginning, they have some pre-conceptions about teaching that they confirm or discard. Finally, pre-service teachers provide emotional support and mutual motivation to each other (Comoglu and Dikilitas, 2020). The issues briefly narrated above correspond to face-to-face classes.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Partnerships among PSTs, mentor teachers, and teacher educators in AR studies have been advocated by many scholars (Hagevik et al, 2012) but research has shown that collaboration can be undermined by weak communication between different stakeholders (e.g., Burbank & Kauchak, 2003;Çomoglu & Dikilitaş, 2020;Darwin & Barahona, 2019;Jakhelln & Pörn, 2019;Ulvik, 2014;Ulvik & Riese, 2016). For example, to better understand the challenges of supporting and assessing PSTs' AR projects in the context of university-school collaboration, Jakhelln and Pörn (2019) examined the experiences of ten PSTs and found that teacher educators and practicum teachers tended not to contact each other, i.e., they avoided boundary crossings.…”
Section: Weak Communication In Partnershipsmentioning
confidence: 99%
“…To exemplify, Hendry et al (2021) report that their study with teachers conducting peer-observation demonstrates that this activity enhances their practice. Moreover, Comoglu and Dikilitas (2020) highlight the role of verbally recorded reflections on developing mutual motivation, deepening ideas, and providing mutual support in Peer Practicum.…”
Section: Introductionmentioning
confidence: 99%